2020
DOI: 10.1021/acsomega.0c01388
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Inverted Five-Spot Reservoir Simulation at High Water-Cut Stage Based on Time-Varying Relative Permeability Curves

Abstract: After large-scale and long-term waterflooding, reservoir physical properties such as the pore throat structure and rock wettability may change. In this paper, the relative permeability curves under different water injection volumes through core-flood experiments were used to characterize the comprehensive changes of various reservoir physical properties at high water-cut stage. The novel concept of "water cross-surface flux" was proposed to characterize the cumulative flushing effect on the reservoir by inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The object selected for modelling is a part of a reservoir with dimensions 1500 by 1500 meters and a production well positioned in the centre. As part of the reservoir pressure maintenance system (RPMS), four injection wells were added to the model according to a five-spot pattern (Davies & Silberberg 1968;Hofmann, Al-Obaidi & Kamensky 2021;Sun, Liu, Wang et al 2020) at equal spacing from the central well, with a grid density of 25 ha per well. In the design, the wells were expected to last 30 years.…”
Section: Methodsmentioning
confidence: 99%
“…The object selected for modelling is a part of a reservoir with dimensions 1500 by 1500 meters and a production well positioned in the centre. As part of the reservoir pressure maintenance system (RPMS), four injection wells were added to the model according to a five-spot pattern (Davies & Silberberg 1968;Hofmann, Al-Obaidi & Kamensky 2021;Sun, Liu, Wang et al 2020) at equal spacing from the central well, with a grid density of 25 ha per well. In the design, the wells were expected to last 30 years.…”
Section: Methodsmentioning
confidence: 99%
“…Water flooding is the most widely used method of improving the ultimate oil recovery (IOR) including artificial water flooding and natural water flooding [3][4][5][6][7][8][9]. However, in the process of water flooding development, the decrease of reservoir temperature and pressure and the change of fluid properties lead to the break of the equilibrium, which affects the development of the oilfield [10]. The erosion of injected water causes physical changes in reservoir structure, and the incompatibility between injected water properties and reservoirs causes chemical effects such as water swelling, crystallization, precipitation, and dissolution of special minerals in reservoirs [11].…”
Section: Introductionmentioning
confidence: 99%
“…The water cut of the oil field has been rising after a long period of water flooding development. Enhancing liquid for oil increment is an effective way to sustain stable production and improve recovery factors in the mid-late life of reservoirs developed by water flooding (Feng et al, 2013;Liu et al, 2017;Sun et al, 2020). Many scholars have found that increasing the displacement pressure difference can improve the oil displacement efficiency through microscopic displacement experiments by CT and microfluidic technology (Zhang et al, 2017;Zhu et al, 2017;Liu et al, 2021;Tan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%